A migração dos mortos: remanejamento de cemitérios na região do Lago de Itaipu - Melchior, Kleber Dreicy (2012)
This dissertation aims to engage with the relations of territorial belonging, in order to understand how it presents itself and what its relevance with the local society. The Paraná western region is the starting point of this observation and the search for references on this telluric took from the experiences of the dispossessed in the region where today defines the artificial Itaipu Lake. For example the link between man and territory, we used the cemetery of the Alvorada do Iguaçu former village, that was border district of Foz do Iguacu city during the construction of the Itaipu binational dam. The memory of former residents of the locality, as well as their experiences, is explored in order to answer questions about the relevance of the relationship between the individual, their territory and the construction of their identity process, as well as the identity of the environment which it belongs. Dealing with the dead is studied for the understanding of potential territorial disruptions and changes in environment shared geographical and socioculturally.